THE IMPORTANCE OF INDEPENDENT LEARNING IN IMPROVING THE QUALITY OF TEACHING - Hayitova Shakhnoza Daniyarovna (Journals Park Publishing, 2022)
This article outlines the content, ways of organizing students' independent learning, the types and objectives of independent learning.  It also reveals the levels and criteria of independent learning activities, the stages of implementation of independent learning, the ways of developing skills and competence of working independently, as well as the degrees of independent learning.
Keywords: education; creative; degree